2022
DOI: 10.1155/2022/5864826
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A1 Overexpression Is Involved in Energy Metabolism Reprogramming to Induce Tumor Progression in Epithelial Ovarian Cancer and Is Associated with Immune-Infiltrating Cells

Abstract: Cationic amino acid transporters (SLC7A1/CAT1) are highly expressed in human ovarian cancer (OC) tissues. However, the specific biological functions and mechanisms involved remain unclear. We used bioinformatics analysis to explore SLC7A1 expression level, prognostic value, and tumor mutation burden (TMB) in ovarian cancer (OC) tissues. We performed in vitro experiments to identify the expression and biological function of SLC7A1 in epithelial ovarian cancer (EOC) tissues and cells. An amino acid autoanalyzer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…CAT-1 is overexpressed in EOC and it is involved in transporting phenylalanine and arginine. The expression of CAT-1 is associated with poorer survival rate in EOC patients and it was shown to promote proliferation and migration in EOC [182]. Arginine is synthesized de novo by the urea cycle.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…CAT-1 is overexpressed in EOC and it is involved in transporting phenylalanine and arginine. The expression of CAT-1 is associated with poorer survival rate in EOC patients and it was shown to promote proliferation and migration in EOC [182]. Arginine is synthesized de novo by the urea cycle.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Reduced expression of DHRS3 has been previously shown in gastric cancer, and its ectopic expression was found to inhibit cell proliferation and migration (Sumei et al, 2021). Expression of genes involved in glucose metabolism such as HKDC1 (Zapater et al, 2022) and amino acid metabolism such as SLC7A1 (You et al, 2022), were elevated, suggesting an impact of tyramine on cell energy metabolism.…”
Section: Tyramine Affected Dna Organization and Oxidative Respiration...mentioning
confidence: 77%
“…3.1 | SLC7A1 is highly expressed in the stroma of HGSOC Our previous bioinformatics analysis showed that overexpression of SLC7A1 was correlated with decreased progression-free survival (PFS) in OC patients, and SLC7A1 expression in OC was closely correlated with CAFs (p < 0.05). 20 To further clarify the relationship between SLC7A1 and the interstitial of ovarian cancer, immunohistochemical results showed significant SLC7A1 interstitial deposition in HGSOC samples (Figure 1A). However, perhaps due to the small number of immunohistochemical cases, we did not find significant differences in the expression of SLC7A1 in different stages of HGSOC.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous studies have shown that SLC7A1 is highly expressed in EOC cells and is involved in tumor progression, platinum resistance, and amino acid metabolic remodeling in EOC, and is associated with poor progression‐free survival (PFS) in OC patients. 20 Meanwhile, the database evaluation found that there was a significant positive correlation between SLC7A1 and CAFs in OC ( p = 0.00015). However, the expression and mechanism of SLC7A1 in CAFs remain unclear.…”
Section: Introductionmentioning
confidence: 97%